The Effectiveness of Hypnobirthing Practices and the Use of Whatsapp Groups in Increasing Pregnant Women's Knowledge of Hypnobirthing - Paruhum Tiruon Ritonga; Urhuhe Dena Siburian (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Approaching childbirth, physiologically, the mother experiences fear, anxiety and worry which, if excessive, can increase the risk that can harm the mother and fetus, so the mother needs relaxation, one of which is hypnobirthing. During a pandemic, social media can be utilized, namely the WhatsApp Group. This study aims to find out whether there are differences in the effectiveness of hypnobirthing practices compared to using WhatsApp Groups in increasing pregnant women's knowledge about hypnobirthing. The type of research is experimental, namely quasi-experimental (quasi-experimental) by giving treatment to hypnobirthing practices and using WhatsApp Groups, each consisting of 15 pregnant women. Data collection was carried out during the class of pregnant women in Sitompul Village, Panggabean Village and Simorangkir Village. Univariate analysis method by looking at the factors and distribution of the independent and dependent variables. Bivariate analysis to determine the relationship between the two variables. The effectiveness of the treatment is known by the T test to see which factors are most effective in influencing knowledge. The results showed that the majority of respondents were of healthy reproductive age (20-35 years), third trimester of pregnancy, primi para and multipara, housewife occupations. Hypnobirthing practice is effective in increasing knowledge with p-value = 0.000 <0.05. The use of WhatsApp groups is effective in increasing knowledge with p-value = 0.009 <0.05. There is no difference in the effectiveness of hypnobirthing practices and the use of WhatsApp Groups in increasing knowledge with the Mann Whitney T test where p-value = 0.446 >0.05). It was concluded that there was an increase in knowledge about hypnobirthing after implementing hypnobirthing practices and after becoming a member of the WhatsApp Group. There is no difference in increasing knowledge of hypnobirthing practices by using WhatsApp Groups. Keywords: Hypnobirthing, Knowledge, Practice, WhatsApp Group